HUBUNGAN SIMULTAN SUMBER PENERIMAAN DAERAH, BELANJA MODAL DAN IPM TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN - Putri Vialeta; Azwardi Azwardi; Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2015)
The objective of this research was to investigate and analyze the Simultaneous Relationship of Regional Revenue Sources, Capital Expenditure, and HDI toward the Economic Growth in the Province of South Sumatra. The data used in this study were the panel data. The samples of the study were 15 regencies/cities in the period of 2008 – 2013. The analysis technique was the Two – Stage Least Squares (TSLS) by using the eviews 7 program. The estimation of the first simultaneous equation showed that Capital Expenditure and HDI simultaneously had a significant positive influence on the Economic Growth with the F probability value of 0.000000 < 0.05 (Î± = 5%), while the estimation of the second simultaneous equation indicated that the Local Own – Source Revenue, Revenue Sharing Fund, and General Allocation Fund Simultaneously had a significant positive influence on the Capital Expenditures with the probability value of 0.000000 < 0.05 (Î± = 5%). Keywords: Local Own – Source Revenue, Revenue Sharing Fund, General Allocation Fund, Capital Expenditures, HDI, and Economic Growth